Levels of physical activity and time spending in front of screens in schoolchildren: differences in age and gender - Portela-García, Cristina Andrea; Vidarte-Claros, Armando (Universidad y Salud, 2021)
Introducción: Use of electronic screen technologies are increasingly widespread among children and their frequent use has led to a sedentary lifestyle that increases health risks in this population. Objective: To study the association of physical activity and the use of electronic screen devices with the body mass index (BMI) and gender in urban schoolchildren aged between 10 to 12 years from the city of Popayán (Cauca, Colombia). Materials and methods: A comparative prospective cross-sectional study, with univariate and bivariate analyses, was carried out using a simple random sampling of 440 students between the ages of 10 and 12 years (220 boys / 220 girls). The Physical activity Questionnaire for Older Children (PAQ-C) was applied. Results: There is an association between moderate levels of physical activity and hours spent in front of electronic screen devices (X2 =598.6; p=0.00). Likewise, an association between the level of physical activity and gender of schoolchildren was found (X2 =13.551; p= 0.004). Conclusions: Children who frequently use television, computers, and/or video games show low to moderate levels of physical activity.